Acinetobacter baumannii represses type VI secretion system through a manganese-dependent small RNA-mediated regulation - Somok Bhowmik; Avik Pathak; Shivam Pandey; Kuldip Devnath; Abhiroop Sett; Nishant Jyoti; Timsy Bhando; Jawed Akhter; Saurabh Chugh; Ramandeep Singh; Tarun Kumar Sharma; Ranjana Pathania (mBio)
ABSTRACT Type VI secretion system (T6SS) is utilized by many Gram-negative bacteria to eliminate competing bacterial species and manipulate host cells. Acinetobacter baumannii ATCC 17978 utilizes T6SS at the expense of losing pAB3 plasmid to induce contact-dependent killing of competitor microbes, resulting in the loss of antibiotic resistance carried by pAB3. However, the regulatory network associated with T6SS in A. baumannii remains poorly understood. Here, we identified an Mn2+-dependent post-transcriptional regulation of T6SS mediated by a bonafide small RNA, AbsR28. A. baumannii utilizes MumT, an Mn2+-uptake inner membrane transporter, for the uptake of extracellular Mn2+ during oxidative stress. We demonstrate that the abundance of intracellular Mn2+ enables complementary base pairing of AbsR28-tssM mRNA (that translates to TssM, one of the vital inner membrane components of T6SS), inducing RNase E-mediated degradation of tssM mRNA and resulting in T6SS repression. Thus, AbsR28 mediates a crosstalk between MumT and T6SS in A. baumannii.IMPORTANCESmall RNAs (sRNAs) are identified as critical components within the bacterial regulatory networks involved in fine regulation of virulence-associated factors. The sRNA-mediated regulation of type VI secretion system (T6SS) in Acinetobacter baumannii was unchartered. Previously, it was demonstrated that A. baumannii ATCC 17978 cells switch from T6− to T6+ phenotype, resulting in the loss of antibiotic resistance conferred by plasmid pAB3. Furthermore, the derivatives of pAB3 found in recent clinical isolates of A. baumannii harbor expanded antibiotic resistance genes and multiple determinants for virulence factors. Hence, the loss of this plasmid for T6SS activity renders A. baumannii T6+ cells susceptible to antibiotics and compromises their virulence. Our findings show how A. baumannii tends to inactivate T6SS through an sRNA-mediated regulation that relies on Mn2+ and retains pAB3 during infection to retain antibiotic resistance genes carried on the plasmid.